(untitled) (Canadian Medical Education Journal, 2022)
• The transition from undergraduate medical education (UGME) to postgraduate medical education (PGME) is a time of vulnerability for medical schools, postgraduate residency programs, and most importantly, trainees • There is a disconnect between the UGME and PGME experience. Student information shared by UGME is primarily summative of knowledge and skills; PGME programs are unaware of specific learner accommodation requirements, tailored supervisory needs, or potential professionalism concerns identified during UGME • This lack of integration between UGME and PGME increases potential risk to learners, postgrad programs and patients • Better linkages and communication along the education continuum could optimize learning and reduce inefficiency and risk • The Medical Council of Canada (MCC) has asked if there is a role for a learner handover (LH) within their licensing processes; however the intended purpose of an LH must first be determined • A Canadian-based LH referred to as a Learner Education Handover (LEH) model including disclosure of student learning/disability accommodation needs, general health concerns, EDI/religious requirements, professionalism concerns, recommendations for special focus in residency of specific areas of medical knowledge/skill is described. • Findings from beta and pilot testing support the value and feasibility of the LEH model • Fundamental principles are outlined: • LEH occurs post-residency match • LEH should be forward facing; focused on ongoing or recurring learner issues and needs • Learners must be included in the process • Implementation would require participation by all Canadian medical schools and all learners • Implementation challenges include: • Ensuring learner safety following information disclosure • Engaging UGME Deans • Protection of information ensuring a ‘need-to-know’ status is maintained • Incorporating the LEH into the licensing activity could enable the MCC to support a system that proactively responds to learner needs, optimizes physician performance and promotes safe, high quality patient care.